AB0922 BUROSUMAB (ANTI-FGF23 MONOCLONAL ANTIBODY) IN THE TREATMENT OF A PATIENT WITH RECURRENT TUMOR INDUCED OSTEOMALACIA. (13th June 2020) - Crotti, C.; Zucchi, F.; Messa, P.; Caporali, R.; Varenna, M.
Abstract : Background: Tumor-induced Osteomalacia (TIO) is a rare paraneoplastic syndrome caused by tumoral overproduction of fibroblast growth factor 23 (FGF23), resulting in hyperphospaturia, hypophosphatemia and osteomalacia. Surgery is the only curative treatment, but tumor can locally recur, even after years from primary surgery. Furthermore, some tumors cannot be removed by surgery due to their location. Objectives: To describe a case of a 53-year-old woman affected by recurrent TIO after three surgical attempts of removal treated with Burosumab. Methods: We describe the case of a 53 years old woman with TIO treated with Burosumab, an anti-FGF-23 monoclonal antibody at present approved for X-linked hypophosphatemic rickets only. Results: A 46-year-old Caucasian female was referred to our Bone Unit after experiencing several fractures in different sites. She reported being in good health until three years prior consultation. At the time of symptoms onset, she experienced a progressive muscle pain, enabling her to stand for a long period. During imaging evaluation for atraumatic fracture of right great trochanter, the MRI abdomen and 18 FDG- PET-CT showed a metabolic pre-sacral lesion. She unsuccessfully underwent to an exploratory laparotomy of that lesion. Then, she suffered from atraumatic intertrochanteric fracture of right femur, surgically treated, and after 3 months, she had an insufficiency dyaphiseal fracture of the left femur, surgically treated. Furthermore, she experienced several ribs fractures. At the time of first evaluation, lab works showed: serum-Phosophate (PS) 1.2 mg/dL (reference range (RR) 2.5-4.5 mg/dL), urinary-phosphate of 24h (PU) 842 mg/24h, alkaline phosphatase (ALP) 565 UI (RR<300), 1, 25(OH)2 vitamin D3 27 ng/L (RR 25-86.5), PTH 24 (RR<75 pg/mL), intact-FGF-23 117 (RR 25-45 pg/mL), normal serum and 24h-urinary Calcium. Patient underwent to 68 Ga-DOTATATE-PET-CT that showed a pre-sacral lesion, who was studied with MRI and CT before surgery. In 2013 patient underwent surgical excision of the pre-sacral region. After 18 months of well-being, patient complained worsening of articular pain and muscle weakness, and further ribs fractures. Another 68 Ga-DOTATATE-PET-CT reported a relapse of the previous pre-sacral lesion (32x12x47 mm) with an increase of FGF-23levels (54.6 pg/mL). Even the subsequent surgery was not able to remove the tumor. Since 2015, patient was maintained in phosphorus supplements and 1, 25(OH)2 vitamin D3, but PS levels never normalized. We asked for compassionate use of Burosumab and, after ethical committee approval, in September 2019 she was started on Burosumab, at a dose of 30 mg per month (0.3 mg/kg). At baseline, she had PS 1.2 mg/dL, PU 1874 mg/24h, TRP 25.96%. After two months, she improved in pain symptom (VAS reduction from 65 to 12 mm), which allow her to walk and stand without crutches. She did not normalize her PS levels (1.3 mg/dL), while PU reduced to 1000 mg/24h. We titred Burosumab dose at 40 mg per month (0.6 mg/kg) and patient is still under therapy, waiting for next blood works. Conclusion: This is the first European patient affected by TIO treated with Burosumab. Burosumab could be a promising therapy in the medical treatment of TIO refractory or not eligible for definitive surgery. Further data are needed to standardize the proper dose regimen. Disclosure of Interests: Chiara Crotti: None declared, Francesca Zucchi: None declared, Piergiorgio Messa: None declared, Roberto Caporali Consultant of: AbbVie; Gilead Sciences, Inc.; Lilly; Merck Sharp & Dohme; Celgene; Bristol-Myers Squibb; Pfizer; UCB, Speakers bureau: Abbvie; Bristol-Myers Squibb; Celgene; Lilly; Gilead Sciences, Inc; MSD; Pfizer; Roche; UCB, Massimo Varenna: None declared